Study of Nutritive Value of Oil Palm Frond Silage with Molasses - ไกรพรม เทียนทิพย์; จันทรัตน์ สิทธิศักดิ์; หมาดทิ้ง ปัทมา; ดือราซอ ฮามีน๊ะ (YRU Journal of Science and Technology, 2018)
The chemical composition of oil palm frond, oil palm frond petiole and oil palm leaf were 34.12, 25.04 and 44.97% of dry matter (DM) 3.32, 1.20 and 8.12% of crude protein (CP), 44.67, 47.07 and 49.54 % of neutral detergent fiber (NDF), respectively. The chemical composition of the supplement molasses in oil palm frond at 0, 3, 5 and 7% on fresh basis respectively to prepare oil palm frond silage, with 5 replicates each was employed. The total of fermented bags were opened at 30 day. The results of these study showed that all of treatments were yellow and green. The supplement molasses in oil palm frond at 3, 5 and 7% gave acetic acid and butyric acid and was significantly lower than 0% (P<0.05). Moreover, the crude protein of 5 and 7% molasses was significantly higher than 3 and 0%, respectively (P<0.05). The optimum level of supplement of molasses with oil palm frond was 7% to feed ruminant.